Error estimates of theoretical models: A guide - Dobaczewski, J.; Nazarewicz, W.; Reinhard, Paul-Gerhard (Journal of Physics G: Nuclear and Particle Physics, 2014)
This guide offers suggestions/insights on uncertainty quantification of nuclear structure models. We discuss a simple approach to statistical-error estimates, strategies to assess systematic errors, and show how to uncover inter-dependences by correlation analysis. The basic concepts are illustrated through simple examples. By providing theoretical error bars on predicted quantities and using statistical methods to study correlations between observables, theory can significantly enhance the feedback between experiment and nuclear modeling. © 2014 IOP Publishing Ltd.
CRIS-Team Scopus Importer:2023-07-24
Keywords: correlation analysis; error estimates; error propagation; modelbased extrapolations; nuclear models; regression analysis; systematic and statistical errors; uncertainty quantification